SYNTHESIS OF BIS-DICHLORODIAZADIENE FROM 2,3,5,6-TETRAFLUOROTHEREPTHAL ALDEHYDE - Mammadova Aynur Teyyub; Mehdiyeva Samira Tofig; Fataliyeva Narmin Malik; Rasulzade Lala Rovshan; Bayramova Aytac Ganimet (Progress in Science, 2024)
Development of effective synthesis methods of new polyfunctional compounds based on catalytic reactions in organic synthesis is one of the urgent issues. In these syntheses, the functionalization of any group in the substrate or the introduction of new functional groups, intramolecular and intermolecular heterocyclization as a result of the interaction of 2 or more groups, the formation of new C-C, C=C, C=N, C-N, C-Hal bonds, etc. such interesting transformations are used.